1991
DOI: 10.1002/ajim.4700190103
|View full text |Cite
|
Sign up to set email alerts
|

Implications of OSHA's reliance on TLVs in developing the air contaminants standard

Abstract: (RELs) were available for 59 of these substances. The ratio of PEL to REL ranged up to 1,000, with a median of 2.5 and a mean of 71.4. OSHA excluded 42 substances from the standard altogether despite the availability of NIOSH RELs, solely because no TLV had been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…[25][26][27][28] The TLV for chloropicrin is based upon WWI-era studies with human volunteers, 6,22 but is not based upon a no-effect level. The 8-h time interval used in the standard represents another deficiency: peak levels causing acute irritation can easily be obscured within an 8-h interval with an average exposure at or below the 0.1 ppm standard.…”
Section: Regulatory Controls On Chloropicrin Exposurementioning
confidence: 99%
“…[25][26][27][28] The TLV for chloropicrin is based upon WWI-era studies with human volunteers, 6,22 but is not based upon a no-effect level. The 8-h time interval used in the standard represents another deficiency: peak levels causing acute irritation can easily be obscured within an 8-h interval with an average exposure at or below the 0.1 ppm standard.…”
Section: Regulatory Controls On Chloropicrin Exposurementioning
confidence: 99%
“…NBOSH, like most other national authorities in Europe, publish a new version of their list of exposure limits every 1-3 years. The national American authority, OSHA, has failed-in spite of repeated attempts-to update its values, due to the massive judicial process that follows every single change of an exposure limit (Hansson, 1998:18-20;Paull, 1984;Robinson et al, 1991;Paustenbach, 1997).…”
Section: Regulationmentioning
confidence: 99%
“…However, beginning in the late 1980s, criticism about non-scientific considerations being used to set TLV's suggested that TLVs might not offer sufficient health protection to workers. The criticism, which voiced internationally [Castleman and Ziem, 1988;Ziem and Castleman, 1989;Roach and Rappaport, 1990;Robinson et al, 1991] and in the Netherlands [Ulenbelt, 1991;Ulenbelt et al, 1991;Bus and Posthuma, 1992], concerned strong corporate influence in developing TLVs and the quality of the justifications underlying TLVs. This prompted the Dutch Ministry of Social Affairs and Employment to request that the Health Council of the Netherlands reassess the health protection of the MAC values listed in the 1994 Dutch MAC list.…”
Section: Introductionmentioning
confidence: 99%